Improved neurological function in a paediatric patient following Onyx embolization of a cervical glomus arteriovenous malformation. (6th May 2010) - Kitamura, Gene; Jacobson, J Paul; Zouros, Alexander; Neglio, Holly
Abstract : Spinal cord intramedullary arteriovenous malformations (AVMs) pose a therapeutic challenge. Because of their complex angioanatomy, surgical excision of these lesions is difficult at best. Over the past decade, endovascular therapy has been established as an alternative treatment modality. As an embolic agent, N -butyl cyanoacrylate (NBCA) posed several problems such as difficulty of use and unpredictable performance. Onyx (ev3, Irvine, California, USA), an alternative liquid embolic agent, possesses several advantageous properties, such as increased control of agent delivery, over previous embolic agents like NBCA. However, reports of Onyx use in treating spinal intramedullary AVMs are still rare, especially in paediatric patients. We report a paediatric patient with glomus-type spinal intramedullary AVM treated successfully with Onyx with intermediate-term outcome.